Ephesians - Thielman, Frank; Yarbrough, Robert W.; Stein, Robert H. (Grand Rapids, Mich. : Baker Academic, 2010)
Noted New Testament scholar Frank Thielman offers a substantive yet accessible commentary on Ephesians in this latest addition to the award-winning BECNT series. With extensive research and thoughtful chapter-by-chapter exegesis, this beautifully written commentary leads readers through all aspects of the book of Ephesians -- sociological, historical, and theological -- to help them better understand its meaning and relevance. As with all BECNT volumes, Ephesians features the author's detailed interaction with the Greek text. This commentary admirably achieves the dual aims of the series -- academic sophistication with pastoral sensitivity and accessibility -- making it a useful tool for professors, students, and pastors. The acclaimed user-friendly design includes shaded chapter introductions summarizing the key themes of each thought unit. - Publisher.
Introduction to Ephesians -- Prescript and greeting (1:1-2) -- Blessing God who has blessed his people in Christ (1:3-14) -- Thanksgiving for conversion and intercession for understanding (1:15-23) -- From children of wrath to new creation (2:1-10) -- From existence without God to membership in the people of God (2:11-22) -- Paul's divinely given task and his suffering for the Gentiles (3:1-13) -- Paul prays for his readers' inner strength and praises the God who can give it (3:14-21) -- The growth of the church toward unity and maturity (4:1-16) -- A reminder of how to live as new human beings (4:17-5:2) -- Avoiding and transforming the deeds of darkness (5:3-14) -- Wise conduct within the household (5:15-6:9) -- Standing against the strategies of the devil (6:10-20) -- A concluding commendation and a final prayer-wish (6:21-24).
Includes bibliographical references (pages 451-470) and indexes.
Keywords: Bible. -- Commentaries